Fabrication and characterization of PLGA-microparticle loaded with alpha-mangostin - Elsaid Ali, Aimen Abdo (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2013)
Alpha-mangostin (AM) is a lipophilic material and has been reported to have multitherapeutic activities. However, many obstacles have been documented that limit its medical applications. Therefore, this study aimed to encapsulate this compound in PLGA-based mico/nanoparticles using two different protocol namely single and double emulsion solvent evaporation techniques. Different experimental variables had been manipulated during the fabrication processes in order to investigate their effects on the particles' characteristics and to obtain optimized formulations for both employed protocol. Reverse-phase high performance liquid chromatographic method had also been developed and validated for their linearity, precision, accuracy, limit of detection and limit of quantitation for reliable quantification of AM content in the particles. In the double emulsion technique, levels of evaluated factors included polyvinyl alcohol (PVA) concentration, ratio of oil to aqueous phases and emulsification time for both primary and secondary emulsion were optimized by using response surface methodology (RSM). The optimized formula that was prepared by 1% PVA, 1:10 ratio of oil to aqueous phases, and sonicated at 2 and 5 min time for primary and secondary emulsions, respectively, showed an encapsulation efficiency of 39.1%, a particle size of 2.06 μm and with desirable polydispersity index value (0.95). Interestingly, this optimized formula had an aerodynamic diameter of about 784.3 nm that is desirable for pulmonary delivery. Thermal analysis of these microspheres showed a physical conversion of AM from crystalline to amorphous state due to strong hydrogen bonds formed between carboxylic groups of polymeric material and hydrogen groups of AM as shown by FTIR. Thereafter, influences of other factors including AM concentration and type of stabilizer were also studied on the particles features. The resultant microspheres were characterized for their encapsulation efficiency (EE), loading efficiency (LE), particle size (PS), polydispersity index (SPAN), external morphology, in vitro release profile and in vitro cytotoxicity against non-small lung cancer cells line (A549). Our data revealed that replacement of PVA with Tween 20 or Span 20 showed significant decrease in the EE at low AM concentration (1% w/v), while increasing the AM concentration up to 2.5% showed significant increment in LE. Addition of Tween 20 also improved both EE and LE percents. Most of AM-loaded microspheres exhibited cell inhibitory activities close to that of free AM despite their release profile showed sustained release of AM over four weeks with total cumulative release of about 36.9-44.3%. In single emulsion technique, the evaluated experimental variables were type of emulsification process, type of surfactant and PVA concentration. Our data revealed that Tween 20 and Span 20 were unable to stabilize water-in-oil (o/w) emulsion system at the ratio were 1:1 and ultrasonic processor had no disruptive effect on the AM stability. Optimized formula prepared with 1% PVA, 0.3% chitosan hydrochloride and emulsified by ultrasonic processor showed EE of 79.1%, LE of 26.4% and with a diameter of 156.6 nm (based on SEM. Cytotoxicity of these particles (IC50; 24.6 μM) was lower than free AM (IC50; 12.8 μM) that consistent with their cumulative release after same incubation time. Incorporation of chitosan modified zeta potential of the nanoparticles to positive charge. The fabricated particles may be used as promising nano/microcarriers system to deliver AM to the lung cancer tissue.